Edukasi Deteksi Dini Kanker Payudara melalui Pemeriksaan Payudara Sendiri (SADARI) di SMA N 8 Kota Jambi - Nel Efni; Tina Yuli Fatmawati (Jurnal Abdimas Kesehatan (JAK), 2021)
The highest incidence of cancer in Indonesia occurs in women: breast cancer and cervical cancer. The risk of breast cancer increases with age. Even a young age does not guarantee that it is safe from breast cancer. In basic health research, the highest number of cancer patients was Central Java, with 68,638 people with 11,511 cancer patients. Self-Breast Examination (BSE) is an integral part of every woman's breast examination. Breast self-examination is performed once a month and can be an effective screening instrument for breast lesions. The purpose of this activity is to inform breast cancer, its signs and symptoms, causes, prevention and how to detect breast cancer by means of BSE. This service activity was carried out in November 2019- January 2020, at SMA N 8  Jambi City. The target is 30 students. This activity consists of providing education using power point media, leaflets, posters and videos, as well as demonstrations using models. After education, all students can understand and be able to properly demonstrate BSE techniques. It is recommended that students routinely carry out breast self-exams every month so that they can detect early breast cancer symptoms.